(untitled) (Papeles, 2020)
This paper presents the construction of an education program related to environmental education and investigation training for basic secondary students, in addition to the results of the first stage of its implementation. The Delphi method is used to consolidate the group of experts who support the development of the curriculum and its implementation; the techniques of survey and semi-structured interview are also used to support the main methodology. For the analysis of quantitative data, the statistical software SPSS (version 25) by IBM is used. The preliminary results of the first stage of curriculum implementation give indications of a positive change in the perception that students have of research and conceptualization of the environment, attributable to the interdisciplinary construction strategy of the training program.